Hyperthyroidism ye cɔl Diabetes Mellitus Under the Health Promotion Model: Changes in Thyroid Hormones, Glucose-Lipid Metabolism, and Inflammatory Markers - Tang, Miao; Xu, Jiao; Chen, Yanling; Zhou, Bo (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effects of a Health Promotion Model (HPM)-based comprehensive intervention on thyroid hormones, glucose-lipid metabolism, and inflammatory markers in patients with hyperthyroidism (HT) complicated by diabetes mellitus (DM), and to elucidate the potential mechanisms underlying these effects.Methods: A total of 142 patients diagnosed with HT and DM between January 2024 and January 2025 were enrolled. Participants were divided into two groups: the HPM group (n=64), which received a structured HPM-based intervention, and the conventional group (n=78), which underwent standard management. Laboratory assessments were conducted before and after the intervention to evaluate thyroid hormones (FT3, FT4, TSH), glucose-lipid metabolism parameters (fasting plasma glucose [FPG], glycated hemoglobin [HbA1c], total cholesterol [TC], triglycerides [TG]), inflammatory markers (high-sensitivity C-reactive protein [hs-CRP], interleukin-1β/6 [IL-1β/IL-6]), and bone metabolism indicators (osteocalcin [BGP], alkaline phosphatase [ALP], calcitonin [CT]). Data were analyzed using SPSS 24.0.Results: Compared to the conventional group, the HPM group exhibited significantly greater improvements in thyroid function, with more pronounced reductions in FT3 and FT4 (P